2021
DOI: 10.1016/j.iccn.2020.102966
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ perceptions and demands regarding COVID-19 care delivery in critical care units and hospital emergency services

Abstract: Highlights Critical care nurses have had to perform tasks for which they have not received proper training. Nurses have had to manage the fear of becoming infected and spreading it to their families. Moral suffering and emotional exhaustion are major consequences of front-line care. Heavy workloads, high patient-nurse ratios, and lack of rest are causing exhaustion among nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
226
0
16

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(279 citation statements)
references
References 31 publications
14
226
0
16
Order By: Relevance
“…Consistent with our findings, most HCWs in previous studies indicated that the way that their work was organized during the COVID-19 epidemic did not allow them to get enough rest, leaving them feeling exhausted. 20 As pointed out by other authors, 21 22 medical centers need to provide breaks to meet basic needs and allow the venting of emotions.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, most HCWs in previous studies indicated that the way that their work was organized during the COVID-19 epidemic did not allow them to get enough rest, leaving them feeling exhausted. 20 As pointed out by other authors, 21 22 medical centers need to provide breaks to meet basic needs and allow the venting of emotions.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 Accordingly, international studies indicate higher risks of mental and physical health burdens among health care workers during the SARS-CoV-2 pandemic. 3 , 4 These demands are accompanied by a number of other challenges affecting German long-term care facilities in general such as the discrepancy between the availability and need for nursing specialist or individual performance and remuneration. 5 , 6 This results in a continuously high sense of stress and occupational illnesses, and an early exit from the job among the nursing workforce.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses should take care of the patients and monitor their families visiting the hospital at all times. However, many nurses felt heavy workloads and physical and mental burdens during this pandemic [ 11 , 12 , 13 ]. As a result, many nurses might move out or quit their job, inevitably resulting in a shortage of nurses [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%